Exploring CPTED strategies to enhance pedestrian safety in the neighbourhood of Chennai using a structural equation modeling approach - Revathi A; Lakshmi S (Journal of Asian Architecture and Building Engineering)
Neighborhoods act as significant spaces where people engage in diverse actions encompassing working, living, studying, as well as recreation. Henceforth, the walkable neighborhood has been characterised through cleanliness, safety, and maintenance. The urban crime significantly exhibits the insecure feeling among the residents. The crime prevention minimises the occurrence of crimes and elevates security. The prevailing research demonstrates the crime prevention through spatial analysis and predictive modeling. There is limited research in the context of Chennai. The present research adopts CPTED (crime prevention through environmental design) for detection of gaps in the safety strategies. Cross-sectional research has been conducted in Zone XV, Ward 193, Thoraipakkam, Chennai, India. Data were gathered from 400 residents through a semi-structured questionnaire. The goal of the research is to utilise the crime data from the years 2017 to 2023 and examine the fear determinants impacting the pedestrians. Also, it proposes aligned strategies for CPTED to elevate the urban safety as well as liveability in Chennai. The statistical analysis has been conducted through SPSS version 25 and AMOS 26 for assessing the relationship among environmental factors impacting the safety perception. CFA and SEM have been deployed for evaluating the relationship of CPTED parameters, crime.